Topical Rifamycin Prophylaxis in Gynecological and Obstetric Surgery - Nahit Ata; Mehmet Kulhan; Nur Gozde Kulhan; Can Turkler; Ahmet Bilgi; Cetin Celik (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: Antibiotic prophylaxis is one of the most important steps to reduce surgical site infections. First-generation cephalosporin (cefazolin) is used prophylactically in the majority of operations. Rifamycin is a broad-spectrum semisynthetic antibiotic that is bactericidal against gram (+) and gram (˗) microorganisms. To the best of our knowledge, there are no studies on the use of rifamycin in antibiotic prophylaxis. In this study, we aimed to analyze whether there is a difference between the use of only cefazolin and only rifamycin in terms of surgical site infections.